Writing Practices in El-Lahun Papyri during the Middle Kingdom - Nassar, Mohamed A..
El-Lahun papyri have fixed writing systems concerning their form, layout, formulae, orthography, and paleography. Reasons for this are the cultural identity of the scribe, writing practices, scribal habits, and the level of the scribe’s education. In this paper, we discuss the writing practices and scribal habits during the Middle Kingdom in El-Lahun society through the hieratic and the cursive hieroglyphic papyri by studying writing materials, the reuse of papyrus, and traces of palimpsest, layout, traditions of corrections and additions, verse points, blank space, guidelines and borderlines, and check marks. http://dx.doi.org/10.5913/jarce.55.2019.a007